Current treatment of choroidal melanoma. (April 2012) - Tarlan, Bercin; Kiratli, Hayyam
Choroidal melanoma is the most common primary intraocular malignancy in adults. Alternative treatment modalities have been proposed in recent years including enucleation, local resection, plaque brachytherapy, charged-particle radiotherapy, stereotactic photon beam irradiation therapy, transpupillary thermotherapy and photodynamic therapy. This review aims to focus on all the available therapeutic options in choroidal melanoma and update the reader on the current status of each modality. Treatment of choroidal melanomas should be directed towards reducing the risk of recurrences, as it is known that recurrent tumors are associated with an increased rate of metastatic disease and poor prognosis. Advances in genetics and cytogenetics can enhance the accuracy of patient prognostication.